Giant paratesticular dedifferentiated liposarcoma with intraabdominal extension: a case report - Azizi, Muhammad Hasif; Rizuana, Iqbal Hussain; Wong, Yin Ping; Sidek, Khairiyah; Fam, Xeng Inn (Frontiers in Oncology, 2023)
Giant paratesticular liposarcoma is a rare presentation of paratesticular tumour. We present a case of the largest paratesticular liposarcoma described to date with a weight of 4100g and measuring 460 x 210 x 130mm. It was initially mistaken as an inguinoscrotal hernia until a contrast-enhanced computed tomography (CECT) scan of the abdomen and pelvis revealed a huge left paratesticular tumour extending from the scrotum to the mid-abdomen. The challenge was to achieve a tumour-free margin orchidectomy due to the poor fat plane of the tumour to the external iliac artery, psoas muscle, descending colon and anterior abdominal wall. The surgery was started with laparoscopic dissection for the intraabdominal part of tumour from the vital structure, then followed by inguinal